Real sounds influence postural stability in people with vestibular loss but not in healthy controls - Anat V. Lubetzky; Maura Cosetti; Daphna Harel; Marlee Sherrod; Zhu Wang; Agnieszka Roginska; Jennifer Kelly (PLoS ONE, 2025)
Objective What we hear may influence postural control, particularly in people with vestibular hypofunction. Would hearing a moving subway destabilize people similarly to seeing the train move? We investigated how people with unilateral vestibular hypofunction and healthy controls incorporated broadband and real-recorded sounds with visual load for balance in an immersive contextual scene. Design Participants stood on foam placed on a force-platform, wore the HTC Vive headset, and observed an immersive subway environment. Each 60-second condition repeated twice: static or dynamic visual with no sound or static white noise or real recorded subway station sounds [real] played from headphones. Setting Human motion laboratory. Participants 41 healthy controls (mean age 52 years, range 22–78) and 28 participants with unilateral peripheral vestibular hypofunction (mean age 61.5, 27–82) Main outcome measures We collected center-of-pressure (COP, anterior-posterior, medio-lateral) from the force-platform and head (anterior-posterior, medio-lateral, pitch, yaw, roll) from the headset and quantified root mean square velocity (cm/s or rad/s) Results Adjusting for age, the vestibular group showed significantly more sway than controls on: COP medio-lateral (no sound or real with static or dynamic visual); COP anterior-posterior (only on dynamic visuals in the presence of either sound); head medio-lateral and anterior-posterior (all conditions), head pitch and yaw (only on dynamic visuals in the presence of either sound). A significant increase in sway with sounds was observed for the vestibular group only on dynamic visuals COP anterior-posterior and head yaw (real) and head anterior-posterior and pitch (either sound). Conclusions The addition of auditory stimuli, particularly contextually-accurate sounds, to a challenging, standing balance task in real-life simulation increased sway in people with vestibular hypofunction but not in healthy controls. Trial registration Clinical trial registration This study was registered on clinicaltrials.gov at the following link: https://clinicaltrials.gov/study/NCT04479761.